Atomic Data for He-like Tungsten (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2014)
Atomic data on high-Z materials are important for impurity diagnostics due to its possible use in the next generation fusion devices including astrophysics. For this purpose, in the present paper, energies, lifetimes and wave-function compositions have been computed for all level of 1s$^2$, 1s2l,1s3l, 1s4l, 1s5l and 1s6l in highly charged He-like tungsten ion (W LXXIII). Also, we have presented the transition wavelengths, oscillator strengths, transition probabilities and line strengths for the electric dipole (E1) transitions from the levels 1s$^2$, 1s2s and 1s2p. Our reported results have been obtained using the fully relativistic GRASP code including the correlations within the $n = 6$ complex. The validity of the method is assessed through the comparison with the other results previously published. The excellent agreement observed between our new GRASP results and those obtained using different approaches confirm the accuracy of our results.
Keywords: Atomic data; Atomic processes